THE IMPACT OF THE NORTH SUMATRA PROVINCIAL SPORTS CENTRE ON THE ECONOMY AND QUALITY OF LIFE IN BATANG KUIS SUB-DISTRIC - Siti Ramadhani; Salamuddin Nasution (Pena Cendekia Insani, 2025)
This study analyzes the impact of the North Sumatra Provincial Sports Centre on the economy and quality of life in Batang Kuis Sub-district. The research uses a quantitative approach, collecting data through questionnaires from 57 respondents. Descriptive analysis and multiple linear regression were applied to examine the relationship between sports infrastructure development and community welfare. Results show positive impacts, including job creation, increased income, improved road access, and business growth. Despite these benefits, sustainable management is necessary to ensure equitable long-term distribution of the advantages. This research highlights the significant contribution of sports infrastructure to regional economic and social development.